2016
DOI: 10.5771/0032-3470-2016-2-247
|View full text |Cite
|
Sign up to set email alerts
|

Rechtspopulismus in Deutschland. Eine empirische Einordnung der Parteien zur Bundestagswahl 2013 unter besonderer Berücksichtigung der AfD

Abstract: Since its formation, the Alternative für Deutschland (AfD) has been subject to a lively debate. While it has been characterized as 'Eurosceptical' in public, the party is more and more accused of promoting conservative and right-wing positions in terms of societal policy and integration as well as showing anti-establishment attitudes. Based on theoretical work on (right-wing) populism, we deduce a measurement concept that is applied to all relevant parties campaigning in the 2013 Bundestag election by using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 24 publications
1
23
0
8
Order By: Relevance
“…; Franzmann ; Lewandowsky et al. ; Niedermayer ). Importantly, AfD started with a different leadership and programmatic focus compared to what we observe for the years 2015 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…; Franzmann ; Lewandowsky et al. ; Niedermayer ). Importantly, AfD started with a different leadership and programmatic focus compared to what we observe for the years 2015 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have shown that members of parliament not only have different normative ideas about the functioning of democracy, but also assess the democratic status quo very differently (Putnam 1971;1973, 187). Variance of attitudes towards democracy, for instance, in terms of populist attitudes, among candidates is also demonstrated in recent empirical work (Lewandowsky, Giebler, and Wagner 2016;Stavrakakis, Andreadis, and Katsambekis 2016). Against this background, their attitudes towards representative democracy is clearly a relevant topic.…”
Section: Introductionmentioning
confidence: 80%
“…Its main focus steadily shifted towards issues of immigration and integration. Together with its focus on direct democracy measures, Lewandowsky et al (2016) classified the AfD as a classical populist right party.…”
Section: Populist Parties In Comparison: the Cases Of Austria Germanmentioning
confidence: 99%